A PLUM ON THUMB: A RARE PRESENTATION OF SYNOVIAL SARCOMA - Zeb, Junaid; Zafar, Hamza; Khan, Qaisar; Siraj, Muhammad; Khan, Muhammad Ayaz (Journal of Ayub Medical College Abbottabad, 2021)
Synovial sarcoma (SS) is a rare and aggressive mesenchymal tumour accounting for around 5-10% soft tissue neoplasms usually found in joints of upper and lower extremities. A 35years old healthy looking male patient from Afghanistan presented with swelling on palmar side of base of thumb from last one year. Seven months back excisional biopsy was taken report of which showed neurofibroma/dermatofibroma with. No evidence of malignancy seen. From last 5months mass reappeared and gradually increased in size with itching sensation and mild pain. On local examination there was 5×4×5 cm reddish mass on palmar surface of base of thumb with extension into mid thenar eminence with diffuse margins. X-ray showed soft tissue density mass with spikes of calcification. Ultrasound showed 4.2×4×4.5 cm heterogeneous solid lesion on anteromedial surface of root of right thumb without any remarkable intralesional calcification and remarkable intralesional vasculature. MRI reported lobulated well defined soft tissue mass eliciting low to intermediate signal on T1 and WIs and bright signal on T2and STIR Vividly enhancing mass. Case was operated mass was excised and biopsy sent. Post op status was unremarkable. Biopsy reported poorly differentiated biphasic synovial sarcoma. No recurrence seen till 3months.